Kate Chopin in Context
IX, 216 p.
Keywords: Featuring essays by scholars from around the globe, Kate Chopin in Context revitalizes discussions on the famed 19th-century author of The Awakening . Expanding the horizons of Chopin's influence, contributors offer readers glimpses into the multi-national appreciation and versatility of the author's works, including within the classroom setting.